SARKASME DI KALANGAN SANTRI PERSADA UNIVERSITAS AHMAD DAHLAN - Rista, Chika Ardeviya; Sapanti, Intan Rawit (Universitas Ahmad Dahlan, 2022)
This research is motivated by the importance of understanding the forms of sarcasm uttered by students so that the public knows the purpose of using sarcasm. The problems discussed in this study are (1) the form of sarcasm used by Persada UAD 2019/2020 students based on grammar, (2) the form of sarcasm used by Persada UAD 2019/2020 students based on the content of the speech, and (3) the factors causing Persada UAD students to use the form of sarcasm. This study aims to describe the form of sarcasm among Persada UAD students and find out the factors causing Persada students to use sarcasm among Persada UAD students. Based on the research results regarding the form of using sarcasm by Persada UAD students in 2019/2020, the following conclusions were obtained. (1) The use of sarcasm among the students of Persada UAD in 2019/2020 based on the grammatical basis was found in three forms, namely words, phrases, and clauses. (2) The use of forms of sarcasm among Persada UAD students in 2019/2020 based on the content of the speech found seven forms of sarcasm, namely words containing bitterness, bitter reproaches, expressions of anger, swearing, words that are not pleasant to hear, ridicule, and certain social varieties. (3) The factors causing the students of Persada UAD in 2019/2020 to throw sarcasm found ten factors, namely social background, habits, reflexes, anger, inappropriate place and time, inappropriate participants, goals that did not match the speaker, tone when conveying messages, media language, and norms in interaction.